2022
DOI: 10.4314/gmj.v56i3s.12
|View full text |Cite
|
Sign up to set email alerts
|

Urban-rural differences in health service-related factors associated with male involvement in family planning services in Abia State, Southeastern Nigeria

Abstract: Objective: To identify and compare the health service-related factors associated with male involvement in family planning services among the rural and urban areas in Abia State, Nigeria.Design: A community-based cross-sectional study.Setting: Twelve communities (six urban and six rural) in Abia State, NigeriaParticipants: Five hundred and eighty-eight (588) men aged 15-59 years and resident in the study area 6 months before the study were recruited.Main outcome measure: Male involvement in family planning serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…Evidence has shown that man's involvement can lead to contraceptive uptake through the pathway of increased spousal communication [11]. However, family planning programmers have traditionally focused on women as the primary beneficiaries and men have been considered as the silent partners of the services [12]. The concerns that led to the study about the men`s knowledge and attitude are mostly the ideal of family size, gender of children, ideal spacing between childbirth and contraceptive method use are of great influence in women`s preferences and opinions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that man's involvement can lead to contraceptive uptake through the pathway of increased spousal communication [11]. However, family planning programmers have traditionally focused on women as the primary beneficiaries and men have been considered as the silent partners of the services [12]. The concerns that led to the study about the men`s knowledge and attitude are mostly the ideal of family size, gender of children, ideal spacing between childbirth and contraceptive method use are of great influence in women`s preferences and opinions [13].…”
Section: Introductionmentioning
confidence: 99%